Elucidation of colchicine degradation pathways under UVC, UVC/H2O2 and UVC/S2O82− processes: proposed transformation products identification, mechanistic insights and in silico evaluation - Eduardo O. Marson; Gabrielly M. Santos; Lucas G. Costa; Carla F.G. Frois; Raquel W. Becker; Carla Sirtori; Raquel M.F. Sousa; Alam G. Trovó (Chemosphere, 2026)

Chemical and toxicological evaluation of micropollutants degradation in tertiary municipal wastewater by H2O2/UVC - Gabrielly M. Santos; Lucas G. Costa; Eduardo O. Marson; Meliza A.S. Bessa; Raquel W. Becker; Carla F.G. Frois; Carla Sirtori; Adão S. Ferreira; Raquel M.F. Sousa; Waldomiro Borges Neto; Marcelo B. Santos; Solidônio R. Carvalho; et al. (Journal of Environmental Chemical Engineering, 2025)

The impacts of food chains: are alternative food networks sustainable? - S. Falasco; G. Ferla; P. Caputo; B. Mura; B. Borrello; M. Marson; V. León Bravo; F. Caniato (Clean Technologies and Environmental Policy, 2025)
The environmental impacts related to food production are of growing concern, with the phases of production and distribution that significantly contribute to greenhouse gas emissions. Among the call for sustainable food supply chains, Alternative Food Networks (AFNs) have emerged as alternatives to Large-Scale Retail (LSR), striving to promote a more sustainable food system. Research related to AFNs has primarily delved into the importance of local food, connection between producers and consumers or reduce the number of intermediaries. Even if AFNs are widely assumed to be more environmentally sustainable, there is a significant dearth of research on assessing their actual environmental performances. This paper aims to address this aspect of sustainability by analyzing the environmental impacts of AFNs, comparing them to the conventional model of food distribution (LSR), focusing on energy demand and climate change emissions. The study models four scenarios involving the distribution of oranges and carrots, supported by primary data, collected with an extensive interview with one manager for the AFN, and secondary data LSR. Results show that while AFNs perform better than LSR in the upstream logistics, the downstream perform worse, due to less efficient consumer travel patterns. Furthermore, the study evaluates an optimization scenario, revealing that modifying consumers means of transportation could significantly improve AFN performance. In conclusion, the results show how the environmental sustainability of AFNs should not be taken for granted, and how relevant last-mile logistics is for overall environmental sustainability of AFN. The study also provides useful insights for policy development and strategic initiatives aimed at enhancing sustainability and decarbonization in the food sector. Graphical abstract

Enhanced UVC treatment for removal of micropollutants using a combination of the oxidants H2O2 and S2O82– - Lucas G. Costa; Eduardo O. Marson; Gabrielly M. Santos; Waldomiro Borges Neto; Solidônio R. Carvalho; Alam G. Trovó (Journal of Environmental Chemical Engineering, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Drift bottle data hint at large-scale ocean circulation changes - Natasha A. Ridenour; Liam Buchart; Eddy Carmack; Inge Deschepper; Eric Galbraith; Geoff Green; Juliana M. Marson; Clark Pennelly; Tahya Weiss-Gibbons; Paul G. Myers (Frontiers in Marine Science, 2023)
Over the last two decades, in an effort to engage youth in polar science, the Students On Ice (SOI; https://studentsonice.com/ ) project has become a platform for youth to partake in scientific expeditions around the globe. Among the various activities offered, youth are able to join cruises in the North Atlantic or Arctic, and drop sealed glass bottles into the ocean. Of the thousands that have been deployed, 5% of bottles have been recovered and reported back to SOI with details on when and where they were found. Here, we compare the observational bottle data with virtual particle trajectories from a high resolution regional ocean model. Although modelling results indicate a higher likelihood of bottles reaching the shores of the western Atlantic, the majority of recovered bottles were found on the eastern side of the Atlantic. We attribute this disparity to differences in population density in Canada and Europe, biasing the recovery rates. Despite this bias, we find that changes in recovery locations over time are consistent with changes in the main ocean currents associated with the contraction and expansion of the North Atlantic Subpolar Gyre, as simulated in our ocean model. In 2007, a large number of bottles were found in Norway, coinciding with a contracted North Atlantic Subpolar Gyre during 2004-2008. While between 2012-2016, the majority of bottles were recovered on the British Isles, during a time of gyre expansion. These results underline the importance of large scale oceanic cycles for tracking marine debris and pollution, and show how even simple data collection methods, such as drift bottles, can provide clues to the changes in the large scale ocean circulation.

Performance of different peroxide sources and UV-C radiation for the degradation of microcontaminants in tertiary effluent from a municipal wastewater treatment plant - Edna A. Alberto; Gabrielly M. Santos; Eduardo O. Marson; Moisés J. Mbié; Cleiseano E.S. Paniagua; Ivo A. Ricardo; Maria Clara V.M. Starling; José Antonio Sánchez Pérez; Alam G. Trovó (Journal of Environmental Chemical Engineering, 2023)

LP-36: The Clariant CompTox Suite – Towards implementation of predictive toxicology approaches to support discovery of chemical alternatives that are safe and sustainable by design - Q. Li; K. Addis; D. Becker; L. Bodelon; K. Framesqui; M. Hufnagel; A. Marson; F.A. Grimm (Toxicology Letters, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Impact of sea ice transport on Beaufort Gyre liquid freshwater content - Sam B. Cornish; Morven Muilwijk; Jeffery R. Scott; Juliana M. Marson; Paul G. Myers; Wenhao Zhang; Qiang Wang; Yavor Kostov; Helen L. Johnson; John Marshall (Climate Dynamics, 2023)
The Arctic Ocean’s Beaufort Gyre (BG) is a wind-driven reservoir of relatively fresh seawater, situated beneath time-mean anticyclonic atmospheric circulation, and is covered by mobile pack ice for most of the year. Liquid freshwater accumulation in and expulsion from this gyre is of critical interest due to its potential to affect the Atlantic meridional overturning circulation and due to the importance of freshwater in modulating vertical fluxes of heat, nutrients and carbon in the ocean, and exchanges of heat and moisture with the atmosphere. Here, we investigate the hypothesis that wind-driven sea ice transport into/from the BG region influences the freshwater content of the gyre and its variability. To test this hypothesis, we use the results of a coordinated climate response function experiment with four ice-ocean models, in combination with targeted experiments using a regional setup of the MITgcm, in which we rotate the surface wind forcing vectors (thereby changing the ageostrophic component of these winds). Our results show that, via an effect on the net thermodynamic growth rate, anomalies in sea ice transport into the BG affect liquid freshwater adjustment. Specifically, increased ice import increases freshwater retention in the gyre, whereas ice export decreases freshwater in the gyre. Our results demonstrate that uncertainty in the ageostrophic component of surface winds, and in the dynamic sea ice response to these winds, has important implications for ice thermodynamics and freshwater. This sensitivity may explain some of the observed inter-model spread in simulations of Beaufort Gyre freshwater and its adjustment in response to wind forcing.

Emergency response process for sudden rainstorm and flooding: scenario deduction and Bayesian network analysis using evidence theory and knowledge meta-theory - Xiaoliang Xie; Linglu Huang; Stephen M. Marson; Guo Wei (Natural Hazards, 2023)

Environmental conditions influence on the physicochemical properties of wild and cultivated Palmaria palmata in the Canadian Atlantic shore - M. M. M. Vasconcelos; G. V. Marson; S. L. Turgeon; E. Tamigneaux; L. Beaulieu (Journal of Applied Phycology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

A regional Natech risk assessment based on a Natech-prone facility network for dependent events - Mei Cai; Stephen M. Marson (Natural Hazards, 2021)

Disaster diaspora and the consequences of economic displacement and climate disruption, including Hurricanes Matthew (October 8, 2016) and Florence (September 14, 2018) in Robeson County, North Carolina - Stephen M. Marson; Mac Legerton (Natural Hazards, 2021)

Chemical and toxicological evaluation along with unprecedented transformation products during photolysis and heterogeneous photocatalysis of chloramphenicol in different aqueous matrices - Eduardo O. Marson; Cleiseano E.S. Paniagua; Nayara M. Costa-Serge; Raquel M.F. Sousa; Gizele D. Silva; Raquel W. Becker; Carla Sirtori; Maria Clara V. M. Starling; Solidônio R. Carvalho; Alam G. Trovó (Environmental Science and Pollution Research, 2021)

Sex change as a survival strategy - Jennifer D. Gresham; Kristine M. Marson; Andrey Tatarenkov; Ryan L. Earley (Evolutionary Ecology, 2020)

Phenotypically plastic responses to predation threat in the mangrove rivulus fish (Kryptolebias marmoratus): behavior and morphology - W. Ryan James; Joseph M. Styga; Sarah White; Kristine M. Marson; Ryan L. Earley (Evolutionary Ecology, 2018)

NK2 and NK1 receptor-mediated effects of NKA and analogs on colon, bladder, and arterial pressure in anesthetized dogs - Nadia M. J. Rupniak; Mary Katofiasc; Lesley Marson; Karl B. Thor (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Pharmacodynamic evaluation of Lys5, MeLeu9, Nle10-NKA(4–10) prokinetic effects on bladder and colon activity in acute spinal cord transected and spinally intact rats - F. Aura Kullmann; M. Katofiasc; K. B. Thor; Lesley Marson (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Evolution of the deep Atlantic water masses since the last glacial maximum based on a transient run of NCAR-CCSM3 - Juliana M. Marson; Lawrence A. Mysak; Mauricio M. Mata; Ilana Wainer (Climate Dynamics, 2016)

Effect of endogenous and synthetic antioxidants on hydrogen peroxide-induced guinea-pig colon contraction - B. Y. C. Wan; S. Mann; E. S. K. Assem; C. M. Marson (Inflammation Research, 2010)

Effect of antioxidants on airway smooth muscle contraction: action of lipoic acid and some of its novel derivatives on guinea pig tracheal smooth muscle - E. S. K. Assem; S. Mann; B. Y. C. Wan; C. M. Marson (Inflammation Research, 2010)

Mode of action of histone deacetylase inhibitors on mast cell histamine release and colon muscle contraction - K. H. Peh; B. Y. C. Wan; E. S. K. Assem; J. B. Middleton; J. Dines; C. M. Marson (Inflammation Research, 2009)

Effects of a selection of histone deacetylase inhibitors on antigen- and agonist(s)-induced tracheal smooth muscle contraction - E. S. K. Assem; K. H. Peh; B. Y. C. Wan; J. Dines; B. J. Middleton; C. M. Marson (Inflammation Research, 2009)